Social representations of primary school children’s families about Aprende en Casa strategy during the Pandemic - Roncancio, Diana L.; Acosta, Erika A.; Reyes Gómez, Liliana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: The objective of this research exercise is to understand the social representations (SR) of families in the city of Bogota about the Learn at Home Strategy. Originality: This research exercise seeks to contribute to the field of Educational Sciences and pedagogical practices in contexts of crisis and change, describing the relationship between psychological, social and educational processes during the "mandatory preventive isolation" as a consequence of the declaration of the pandemic by COVID-19. Method: This research is framed in the historical-hermeneutic approach, using qualitative construction and analysis tools in four moments: 1) Research approach, 2) Construction of the information, 3) Systematization and organization of the data and 4) Analysis of the social representations. Strategies / information gathering: Autobiographical reports constructed from the everyday accounts of the researchers and participants, containing condensed, expanded, theoretical and methodological notes. The reports were analyzed by means of matrices of categories and subcategories with which the core-periphery diagram of the SRs was subsequently constructed, taking into account the frequency of appearance of texts associated with the subcategories. Conclusions: The 7 categories and 23 subcategories constructed show the families' understanding of the purpose of the strategies designed by the educational institutions to give continuity to the processes, however, they show the difficulties experienced at home due to the confusion between time and study/leisure activities, maintaining the children's attention, parental availability, among others, which lead to conflicts, unmanaged emotions and even school dropout.